If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+8(3x-4)+19=13-5(2x^6)+4+x=
We move all terms to the left:
-3x+8(3x-4)+19-(13-5(2x^6)+4+x)=0
We do not support expression: x^6
| x+x+29=180 | | 2+4k=10 | | 10+4x=-2x+34 | | 24+8*y-18+5=19 | | 2c=-35*7+7c | | 3x^-12x+20=0 | | x+1/3+x-4/2=5 | | 2x+1=21+4x | | d4–1=2 | | -3x+24x-32+19=13-10x-30+4+x | | 10x+10=15x-10 | | 4x+20=5x+5 | | w/3–1=1 | | 39+y/4=3+y | | w3–1=1 | | 39/4=3+y | | 6x+12-9x=24 | | 38+n+68.4=149.80 | | v/2+5=-3 | | d-1/4=3 | | 4(x+10)=5(x+2) | | 39+y=3+4y | | 0.0695=x-1.95x | | 13+2c=11 | | t/5=25 | | 5v+94+31=180 | | 8x-32=8x-15 | | 5x-35=5(x+3) | | 4a+6a-11+82=180 | | 5/x=2.5/2 | | 7x+3x+10=-2(7x+4) | | -1/9y-5=-6 |